Uit: Het Volk 25 januari 1934 (avondblad). Naar aanleiding van het zendverbod voor de VARA op 27 januari 1934
Uit: Het Volk 25 januari 1934 (avondblad). Naar aanleiding van het zendverbod voor de VARA op 27 januari 1934.